The effect of exchange rate changes on trade in East Asia - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2011)
This paper considers how exchange rates affect East Asian trade. The evidence indicates that exports produced within regional production networks depend on exchange rates throughout the region while labor-intensive exports depend on exchange rates in the exporting country. These results make sense since the majority of the value-added of processed exports come from imported parts and components while most of the value-added of labor-intensive exports comes from the domestic economy. Recent findings also indicate that imbalances between the People's Republic of China (PRC) and the United States are a major outlier and that an appreciation of the PRC yuan (CNY) is necessary to reduce these imbalances.
Keywords: F32; F41; 330; Wechselkurs; Volatilität; Zahlungsbilanzungleichgewicht; Außenhandelseffekt; Asien